Enforcement spillovers under different networks: The case of quotas for persons with disabilities in Brazil - Samuel G. Berlinski; Jessica Gagete-Miranda (Inter-American Development Bank (IDB), 2024)
This study examines labor law enforcement spillovers in Brazil's highly informal economy, focusing on disability quota enforcement for formal firms. New inspection procedures increased compliance through heightened inspections and fines, boosting disability hiring. We investigate spillover effects across various firm networks: neighborhood, ownership, and human resources specialists. Results show that spillovers can have up to twice the impact on disability employment compared to direct fines. These findings highlight the potential for targeted enforcement strategies to amplify policy effectiveness beyond directly affected firms even in developing economies characterized by low compliance with employment laws.
Keywords: I38; J68; K31; 330; Enforcement spillovers; Networks; Persons with disability; Brazil